Profit Planning Analysis Of Business To Know The Source Of Mulya Bengkulu City - Agustina Agustina; Wagini Wagini; Tito Irwanto (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
The purpose of this research is to find out how to plan the profitability of the Tahu Sumber Mulya business in Bengkulu City. This type of research involves collecting data through surveys or interviews. The analytical method used in this study is the calculation of Break Even Point, Profit Contribution, Contribution Ratio, Margin of Safety, Company Profit Level, and Company Profit Level. The results show that the Break Even Point (BEP) was achieved at a sales volume of 3,735 units in October 2021. If you donated 42% of your earnings to charity in the last year, your donation would be $99,907.50. The level of safety or Margin of Safety is 1.76%. The company has made a profit of Rp. 2426250.